Denunciation and doxing: towards a conceptual model of digital vigilantism. Issue 3 (1st October 2020) - Trottier, Daniel
ABSTRACT: Individuals rely on digital media to denounce and shame other individuals. This may serve to seek justice in response to perceived offences, while often reproducing categorical forms of discrimination. Both offence taking and its response are expressed online by gathering and distributing information about targeted individuals. By seeking their own form of social and/or criminal justice, participants may supersede institutions and formal procedures. Yet digital vigilantism includes shaming and other forms of cultural violence that are not as clearly regulated. They may feed from state or press-led initiatives to shame targets, or simply to gather information about them. Digital vigilantism remains a contested practice: Terms of appropriate use are unclear, and public discourse may vary based on the severity of the offence, the severity of response, and on participants' identities and affiliations. This paper advances a conceptually informed model of digital vigilantism, in recognition of its coordinated, moral and communicative components. Drawing upon literature on embodied vigilantism as well as concurrent forms of online coordination and harassment, it considers recent cases in a global context in order to direct subsequent analysis of how digital vigilantism is rendered meaningful.